(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Cyanobacteria are photosynthetic prokaryotic microalgae which are found in marine, brackish and freshwater environments and in soils. Cyanotoxins including hepatotoxins and neurotoxins are produced by cyanobacteria commonly found in surface water. The most widely studied hepatotoxins are microcystins and nodularin which were first isolated from Microcystis aeruginosa and Nodularia spumigena, respectively. M. aeruginosa and N. spumigena were cultured and extracted with methanol. The qualitative and quantitative analysis of microcystins and nodularin in cultured cyanobacterial fractions were performed by HPLC. Fluorescein diacetate (FDA) antimicrobial and brine shrimp lethality assay were carried out to determine minimum inhibitory concentration (MIC) and general toxicity of these fractions, respectively. An unusual metabolite named as nodularinol was isolated for the first time from N. spumigena. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21888 Dhaka Univ. J. Pharm. Sci. 13(2): 119-124, 2014 (December)